2023
DOI: 10.7759/cureus.38902
|View full text |Cite
|
Sign up to set email alerts
|

Glucose and Lipid Profiles of Overweight and Obese Children in Riyadh, Saudi Arabia

Mohammed A AlAteeq,
AbdulAziz AlHusaini,
AbdulAziz AlMalahi
et al.

Abstract: Background: Obesity is a prevalent issue worldwide, affecting both children and adults and posing significant health risks. Obesity and overweight are known to be associated with metabolic abnormalities among children and adolescents. This study aims to determine the metabolic profiles, identifying any abnormalities and related factors among overweight and obese children in Saudi Arabia (SA). Methods: This study conducted a cross-sectional, descriptive, and analytical analysis on 382 overweight and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A study on severely obese children and adolescents in the United States, 1999-2012 reported that the prevalence of high TC, low HDL, high triglycerides, high LDL among severely obese adolescents was 16.5%, 40.0%, 30.0%, 13.0%, respectively [22]. A study on obese children in Saudi Arabia found that overweight children had higher HDL levels, while obese children had higher TG levels [23]. In the present study, we found that there were signi cant difference of TG, TC, HDL-C, LDL-C and dyslipidemia prevalence among children and adolescents with or without obesity/overweight.…”
Section: Correlations Between Serum Lipid Concentrations and Food Cat...mentioning
confidence: 99%
“…A study on severely obese children and adolescents in the United States, 1999-2012 reported that the prevalence of high TC, low HDL, high triglycerides, high LDL among severely obese adolescents was 16.5%, 40.0%, 30.0%, 13.0%, respectively [22]. A study on obese children in Saudi Arabia found that overweight children had higher HDL levels, while obese children had higher TG levels [23]. In the present study, we found that there were signi cant difference of TG, TC, HDL-C, LDL-C and dyslipidemia prevalence among children and adolescents with or without obesity/overweight.…”
Section: Correlations Between Serum Lipid Concentrations and Food Cat...mentioning
confidence: 99%